1991
DOI: 10.1177/028418519103200114
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Aspiration Cytology of Enlarged Lymph Nodes

Abstract: Cytological results of US-guided fine needle aspiration biopsies of enlarged lymph nodes from 179patients were analyzed retrospectively. The final diagnoses were benign lymphadenopathy in 90 cases, metastasis in 56, and malignant lymphoma in 33 cases. The material was sufficient for cytological analysis in 174 cases (97.2%). Correct diagnosis of malignant (C IV-V) and benign (C I-II) lymphadenopathy in the whole material was possible in 80 percent of cases. Correct subtyping of lymphoma was possible in 63.6 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
(39 reference statements)
2
23
0
Order By: Relevance
“…Our success rate of 85.2% in obtaining tissue adequate for cytologic or histologic diagnosis is comparable to the rates reported in several other studies of sonographic and CT guided abdominal lymph node biopsies. 3,8,10,11,14,15 Although efficacy and accuracy of FNAB in the diagnosis of metastatic lymphadenopathy from epithelial carcinomas of the gastrointestinal and genitourinary tracts 2,5,7-10,16 and also tuberculous lymphadenopathy 5 are well recognized and documented, cytologic study of lymphomas has generally been regarded as difficult, especially for subtyping. 3,17 However, a number of recent studies have shown that lymph node biopsy is useful and accurate in the diagnosis of lymphoma and its recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our success rate of 85.2% in obtaining tissue adequate for cytologic or histologic diagnosis is comparable to the rates reported in several other studies of sonographic and CT guided abdominal lymph node biopsies. 3,8,10,11,14,15 Although efficacy and accuracy of FNAB in the diagnosis of metastatic lymphadenopathy from epithelial carcinomas of the gastrointestinal and genitourinary tracts 2,5,7-10,16 and also tuberculous lymphadenopathy 5 are well recognized and documented, cytologic study of lymphomas has generally been regarded as difficult, especially for subtyping. 3,17 However, a number of recent studies have shown that lymph node biopsy is useful and accurate in the diagnosis of lymphoma and its recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…3,8,10,11,14,15 Although efficacy and accuracy of FNAB in the diagnosis of metastatic lymphadenopathy from epithelial carcinomas of the gastrointestinal and genitourinary tracts 2,5,7-10,16 and also tuberculous lymphadenopathy 5 are well recognized and documented, cytologic study of lymphomas has generally been regarded as difficult, especially for subtyping. 3,17 However, a number of recent studies have shown that lymph node biopsy is useful and accurate in the diagnosis of lymphoma and its recurrence. 3,18,19 Negative results on FNAB do not always exclude the existence of a pathologic process and should be followed by a repeat procedure with large bore needle or an open biopsy 3,18,19 ; four of our patients with negative FNAB results were finally diagnosed as having malignant lymphomas on excisional nodal biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Needle track seeding by tumor cells in renal mass biopsy is a complication that has been reported 4 times in the past (prior to 1992) when larger (up to 14‐gauge) needles often were used, but had become vanishingly rare. However, a total of 12 additional cases of needle track seeding have been reported with core needle biopsy since 2013, predominantly from Europe . The incidence is not well characterized, but in 1 large meta‐analysis there was 1 case reported in nearly 3000 patients .…”
Section: Introductionmentioning
confidence: 89%
“…We also encountered a single case of malignant melanoma deposits in the inguinal lymph node from a patient with primary malignant melanoma in the ipsilateral foot [11,14]. The smear studied shows scattered pleomorphic cells with few binucleate or multinucleate forms with 1-2 prominent nucleoli.…”
Section: Research Article Tropical Journal Of Pathology and Microbiologymentioning
confidence: 99%